Characteristics and Diagnosis of Pregnancy and Lactation Associated Breast Cancer: Analysis of a Self-Reported Regional Registry - Pugh, Amanda M. (Am J Surg, 2018)
BACKGROUND: Pregnancy-associated breast cancer (PABC) is the most common malignancy in pregnancy. However due to its infrequent occurrence, PABC continues to be poorly understood. METHODS: We performed a retrospective study using self-reported data from 1079 eligible women in a regional breast cancer registry. RESULTS: The PABC cases were more likely than non-PABCs to be younger than age 35 and have nodal involvement at diagnosis. Despite diagnosis at a young age, there was not an association between PABC and family history. For method of diagnosis, PABC was found on self-exam, while non-PABCs were found on mammography. CONCLUSION: In conclusion, PABC is rarely detected by mammography and diagnosis is highly dependent on detection during self-breast exam. Women who are or recently were pregnant should be encouraged to perform regular self-breast exams to report any changes for further evaluation. Patient and clinician education regarding risk and realities of PABC is essential.